1B.12: EFFECT OF OVERCUFFING ON THE ACCURACY OF OSCILLOMETRIC BLOOD PRESSURE MEASUREMENTS. (June 2015) - Padwal, R.; Millay, J.; Babwick, S.; Neil, M.; Langkaas, L.; Ringrose, J.
Abstract : Objective: Overcuffing, or using a blood pressure (BP) cuff that is too large, is known to artificially lower auscultatory BP; however, its effect on oscillometric BP is unclear. The possibility that overcuffing biases oscillometric BP is currently widely disregarded. We performed a two-phase study to confirm that overcuffing lowers auscultatory BP and to assess the effect of overcuffing on oscillometric BP. Design and method: Community-dwelling adults (aged 18y or older) with arm circumferences within the standard range 25–32 cm were recruited. Using primarily the International Standards Organization (ISO) 2009 protocol, we compared the standard Baum adult (25–35 cm) to the large adult (33–47 cm) cuff. The standard cuff was considered the 'reference standard'. In Phase I (auscultatory assessment performed by two trained observers), 87 subjects were recruited to reach the required 255 paired BP determinations. In Phase 2 (oscillometric assessment), 85 subjects were required. Each study phase was analyzed independently using paired t-tests to calculate p-values and by generating Bland-Altman plots. Results: The results of Phase I confirmed that, compared to the standard cuff size, overcuffing reduced auscultatory BP by 3.6 ± 5.1/2.8 ± 4.0 (p-values<0.0001 for both). For Phase 2, the mean age was 39.30 ± 18.3 years, mean arm circumference was 28.0 ± 1.9 cm, 79% were female and 22% had a past history of hypertension. Mean BPs were 112.2 ± 13.1/67.8 ± 7.3 mmHg for the large cuff and 117.8 ± 13.3/71.2 ± 7.1 for the standard cuff (difference of −5.5 ± 5.9/−3.4 ± 5.2; p-values<0.0001). Conclusions: Overcuffing leads to a clinically important downward bias in oscillometric BP. These findings indicate that upper size limits for oscillometric cuffs should be specified.